Characterization of CD41+ cells in the lymph node - Dai, Li; Uehara, Mayuko; Li, Xiaofei; LaBarre, Brenna A.; Banouni, Naima; Ichimura, Takaharu; Lee-Sundlov, Melissa M.; Kasinath, Vivek; Sullivan, Jade A.; Ni, Heyu; Barone, Francesca; Giannini, Silvia; et al. (Frontiers in Immunology, 2022)
Lymph nodes (LNs) are the critical sites of immunity, and the stromal cells of LNs are crucial to their function. Our understanding of the stromal compartment of the LN has deepened recently with the characterization of nontraditional stromal cells. CD41 (integrin αIIb) is known to be expressed by platelets and hematolymphoid cells. We identified two distinct populations of CD41+Lyve1+ and CD41+Lyve1- cells in the LNs. CD41+Lyve1- cells appear in the LN mostly at the later stages of the lives of mice. We identified CD41+ cells in human LNs as well. We demonstrated that murine CD41+ cells express mesodermal markers, such as Sca-1, CD105 and CD29, but lack platelet markers. We did not observe the presence of platelets around the HEVs or within proximity to fibroblastic reticular cells of the LN. Examination of thoracic duct lymph fluid showed the presence of CD41+Lyve1- cells, suggesting that these cells recirculate throughout the body. FTY720 reduced their trafficking to lymph fluid, suggesting that their egress is controlled by the S1P1 pathway. CD41+Lyve1- cells of the LNs were sensitive to radiation, suggestive of their replicative nature. Single cell RNA sequencing data showed that the CD41+ cell population in naïve mouse LNs expressed largely stromal cell markers. Further studies are required to examine more deeply the role of CD41+ cells in the function of LNs.